Analgesic and antihyperglycemic activity evaluation of Bambusa vulgaris aerial parts - A. K. M. Mahmudul Haque, Anuj Kumer Das, Shamrat Shafiul Bashar, Rahat Al-Mahamud, Mohammed Rahmatullah (Journal of Applied Pharmaceutical Science, 2015)
Bambusa vulgaris, also known as ‘Ora Bansh’ in Bangladesh is grown throughout the country for housing and scaffolding purposes. As part of our analgesic and antihyperglycemic plants of Bangladesh screening program, it was of interest to evaluate the analgesic and antihyperglycemic potential of aerial parts of the plant. Methanolic extract of aerial parts (MEBV) at doses of 50, 100, 200 and 400 mg per kg significantly reduced the number of writhings in acetic acid-induced pain model Swiss albino mice by 25.9, 29.6, 37.0, and 44.4%, respectively compared to reductions of 40.7 and 51.9%, respectively, obtained with 200 and 400 mg per kg of a standard analgesic drug, aspirin. MEBV, at doses of 100, 200 and 400 mg per kg also significantly lowered blood glucose levels in mice, respectively, by 32.8, 45.8, and 55.3% compared to control mice. A standard antihyperglycemic drug, glibenclamide, when administered at a dose of 10 mg per kg lowered blood glucose level by 50.8%. Taken together, the results indicate that the aerial parts of the plant possess considerable analgesic and antihyperglycemic potential, which can possibly be attributed to the presence of alkaloids and saponins in the extract.
Keywords: Analgesic, Bambusa vulgaris, antihyperglycemic, Poaceae.